The Importance Of Problem Based Learning Model In Improving Students' Understanding Of Natural Appearances Material - Puspitasari, Regita; Faridah, Tsana Nur; Rustini, Tin (Utami Publisher, 2024)
Problem Based Learning (PBL) is a learning model by solving problems from the knowledge that students have or sources that are already available. This research was conducted using a descriptive method with a qualitative approach. The problem that exists in this study is that students do not understand the material of natural appearance. This study aims to determine the importance of applying the Problem Based Learning model in improving students' understanding of natural appearance material. The results of this study indicate that the Problem Based Learning learning model needs to be applied to students, especially in natural appearance material, because students will better understand and understand related to the material being taught.